Successful therapeutic plasma exchange in post-operative myasthenic crisis in elderly woman - Yalamanchili, Swapna; Narmadha, B (Indian Journal of Case Reports, 2020)
Myasthenia gravis (MG) is a chronic autoimmune neuromuscular disorder that causes weakness of skeletal muscles responsible for breathing and moving parts of the body such as arms and legs. Surgical removal of thymoma may be associated with post-operative myasthenic crisis (POMC). Here, we report the case of a 70-year-old woman treated for squamous cell carcinoma of the uterine cervix, after a span of 11 years, presented with clinical features suggestive of MG. Investigations revealed type AB thymoma. The patient developed POMC, 3 days after the surgical excision procedure. The patient was subsequently treated with therapeutic plasma exchange (TPE), anticholinesterases, and steroids. The TPE in this elderly woman was not associated with any complications and was discharged in complete stable remission. Earlier studies show that many cases have immediate benefits from plasma exchange in MG, particularly MG crisis. TPE is a disease-modifying therapy for MG crisis.